Analysis Of Production Capacity and Raw Materials Towards Profit Maximisation In Okey Sausage Factory - Pesta Gultom; Cynthia Bella; Melyani Melyani; Stephanie Stephanie; Calvin Andriono Abednego (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of production capacity and availability of raw materials on profit maximization efforts at the Okey Sausage Factory. The main problem faced by the company is the limited resources that must be allocated optimally in order to achieve maximum profit levels. This study uses an operations research approach with linear programming methods and simplex methods, which are able to solve optimization problems with two main variables, namely the number of products produced and the amount of raw materials available. The data used include machine capacity, daily raw material quantity, production time, and profit margins for each sausage product. The results of the analysis show that the optimal combination of production capacity and raw materials can significantly increase profits compared to previous production strategies. With the right mathematical model, companies can make more efficient and data-based production decisions.